Tuck everlasting - Babbitt, Natalie (New York Farrar, Straus, Giroux, 1975)
The Tuck family is confronted with an agonizing situation when they discover that a ten-year-old girl and a malicious stranger now share their secret about a spring whose water prevents one from ever growing old.
"An ALA notable children's book."
770L
67735
Keywords: Fantasy; Family secrets; First loves; Girls; Immortality; Musicals; New Hampshire